2007
DOI: 10.1080/13625180601068461
|View full text |Cite
|
Sign up to set email alerts
|

College students in Nigeria underestimate their risk of contracting HIV/AIDS infection

Abstract: College students exhibited an 'optimism bias' associating high rates of HIV risk indicators with low levels of perceived personal risk of infection. This has implications for HIV/AIDS control in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
(10 reference statements)
5
18
0
Order By: Relevance
“…having multiple sexual partners, irregular or no use of condoms even when the sexual contacts were casual partners or CSWs). This finding is consistent with the results of studies conducted among undergraduate students of the universities of Sokoto and Ibadan who stated that no matter what, they could not get AIDS 11,12,16 .…”
Section: Discussionsupporting
confidence: 95%
“…having multiple sexual partners, irregular or no use of condoms even when the sexual contacts were casual partners or CSWs). This finding is consistent with the results of studies conducted among undergraduate students of the universities of Sokoto and Ibadan who stated that no matter what, they could not get AIDS 11,12,16 .…”
Section: Discussionsupporting
confidence: 95%
“…Indeed, the lack of behavior change has been signaled as one of the major challenges in the fight against HIV and AIDS in Uganda [2]. This is one of the common problems, reported in other studies as well [10][11][12][13]. While in some other studies the tendency to underestimate HIV risk has been attributed to misconceptions and low knowledge on HIV transmission [14], in Uganda knowledge about HIV transmission and prevention is generally high [2].…”
Section: Sexual Behaviors Of Secondary School Studentsmentioning
confidence: 96%
“…For instance, a recent study in Nigeria found that while 85% of surveyed students believed they were at little to no risk of HIV infection, 77% were found to actually be at high risk based on behavioral risk assessments (8). Another survey of Kenyan university students found that 69% were sexually active and that 55% reported having first intercourse while attending university (4).…”
Section: Introductionmentioning
confidence: 96%
“…University students in Africa are sexually active and at risk for HIV (4)(5)(6)(7)(8)(9)(10). For instance, a recent study in Nigeria found that while 85% of surveyed students believed they were at little to no risk of HIV infection, 77% were found to actually be at high risk based on behavioral risk assessments (8).…”
Section: Introductionmentioning
confidence: 98%